DETERMINANTS OF Lantana camara IN UDAWALAWE NATIONAL PARK, SRI LANKA - Heenkenda, S; Ranasinghe, S; Madhawa, S (My University, 2016)
The Udawalawa National Park is a Park rich in biodiversity in Sri Lanka. According to the records 650 to 700 Asian elephants (Elephas maximus), endemic flora and fauna were recorded in the Park. In last few decades invasive alien species (IAS) rapidly distributed in large areas of the Park. Among these Lantana camara has shown much dominance and this has significantly reduced the grazing lands of animals with special to elephants. Dearth of information on the factors which determine the prevalence of L. camara has posed a debacle in eradicating the same. This study was therefore undertaken with the primary objective of finding the major determinants of the prevalence of L. camara in the Park using Geographical Information Systems (GIS). Random line transects were used with 84 samples. Number of bushes of L. camara and their coverage was estimated. The inverse distance weighted (IDW) and weighted overlay tools were used to analyse ground survey data. In the sampling points, soil samples were collected and analysed for pH, moisture, type, conductivity and phosphorus content. The results showed that soil pH and coverage of L. camara showed significant positive correlation. Therefore this information will provide valuable insight into the control of the invasive species from the Park. Keywords: biodiversity, geographic information systems, invasive alien species, Lantana camara